Memory Impairment is Associated with Serum Methylarginines in Older Adults - McEvoy, Mark; Schofield, Peter; Smith, Wayne; Agho, Kingsley; A. Mangoni, Arduino; L. Soiza, Roy; Peel, Roseanne; Attia, John (Current Alzheimer Research, 2014)
Background:This study measured serum concentrations of vascular risk factors, asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA) in a representative sample of older community-dwelling adults and determined their associations with objective and subjective memory impairment. Methods: Data on clinical, lifestyle, and demographic characteristics, serum ADMA, SDMA, and L-arginine (measured using LC-MS/MS) were collected from a population-based sample of older Australian adults from the Hunter Community Study. Objective memory was measured with the Audio Recorded Cognitive Screen (ARCS) neuropsychological battery and subjective memory impairment was measured using the Memory Complaint Questionnaire (MAC-Q). Results: Multivariate analysis revealed that SDMA and diabetes were significantly associated with objective memory impairment (Adjusted Odd ratio (AOR) = 3.90; 95% CI. 1.21 – 12.52 for fourth quartile (Q4) of SDMA. ADMA, SDMA, education, number of general practitioner visits and atrial fibrillation were all significantly associated with subjective memory impairment. (AOR = 1.82; 95% CI. 1.04 – 3.18 for Q4 ADMA. Conclusions: Higher serum SDMA was associated with objective and subjective memory impairment while higher serum ADMA was associated with subjective memory impairment.
Keywords: methylarginines